Confinement of nano CdS in designated glass: a novel functionality of quantum dot-glass nanosystems in solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Apte, Sanjay K.; Sonawane, Ravindra S.; Naik, Sonali D.; Patil, Kashinath R. (Journal of Materials Chemistry, 2007)
The present work is the investigation of our novel approach to designing quantum dot-glass nanosystems by confining nano CdS in designated glass and the first employment of such a quantum dot system in solar hydrogen production. The CdS quantum dots were grown in a special glass matrix, which involved a sequence of steps. The obtained glass was of uniformly bright yellow in color and the bulk glass was pulverized to a fine powder of micron size particles. The glass powder was characterized structurally and morphologically. X-Ray diffraction and electron diffraction patterns reveal a hexagonal crystallite system for the CdS quantum dots. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray fluorescence spectroscopy and chemical leaching with HCl studies demonstrate that the 2.5 nm size CdS quantum dots distribute homogeneously in a monodispersed form in the glass domain and on the surface with a ``partially embedded exposure'' configuration. This disposition imparts an excellent photostability against photocorrosion and also a facile catalytic function. Therefore, even a very small amount of CdS quantum dots (0.005 g per gram of glass powder) is able to photodecompose H2S under visible light (lambda >= 420 nm) both in alkaline and pure aqueous media and produce solar hydrogen with markedly high quantum yields of 17.5 and 11.4%, respectively at 470 nm. Salient features like reusability after simple washing, corrosionless-stability and remarkable catalytic activity of this quantum dot-glass nanosystem are brought forth by our novel catalyst design and are much acclaimed in large scale solar H-2 production.